PENANGKARAN ELANG JAWA SEBAGAI SALAH SATU UPAYA PELESTARIAN SATWA YANG DILINDUNGI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract The research aims to study the efforts of Java Eagle preservation, and to study its obÂ¬stacles in the framework of the preservation. The research data was obtained through library and field study. The data was analyzed qualitatively. The research results show that the preservation of the Java Eagle are committed by the protection of that birds, management and conservation their habitat. Meanwhile the obstacles are faced i.e., fiend problem, the weak of the law enforcement, the human resources, and the consciousness society.